Exchange of values in contemporary religious architecture in poland symbol in the dialogue between east and west - Uścinowicz, Jerzy (Journal of Architecture and Urbanism, 2009)
Poland is situated in the area of cultural and religious borderland, in the sphere of Latin and Greek-Slavonic influence. The Author reviews the past and present examples of the exchange of values in the Christian Churches, i.e. the Eastern (Orthodox and Uniate) and the Western (Roman Catholic and Protestant). They are portrayed through mutual conversion of temples, incorporation of traditional orthodox iconography in contemporary Roman Catholic churches as well as by adaptation of historic temples for their mutual ecumenical use. The values give testimony to the synthesis of art of both Christian Churches as well as to the return to their ecclesial unity.Vertybių kaita šiuolaikinėje Lenkijos religinėje architektūroje – dialogo tarp rytų ir vakarų simbolisSantrauka. Lenkija, kalbant apie lotyniškąją ir graikiškąją-slavišką ją įtaką, yra tarsi kultūros ir religijos pasienyje. Autorius apžvelgia praeities ir dabarties  vertybių  kaitos krikščioniškose Rytų (ortodoksai ir unitai) ir Vakarų (Romos katalikai ir protestantai) bažnyčiose pavyzdžius. Jie yra apibūdinami analizuojant abipuses šventovių konversijas, tradicinės ortodoksiškos ikonografijos inkorporavimą į šiuolaikines Romos katalikų bažnyčias, istorinių šventyklų pasisavinimą bendram visuotiniam naudojimui. Vertės liudija abiejų krikščioniškų bažnyčių menų sintezę, taip pat jų grįžimą į dvasinę (ekleziastinę) vienovę.Reikšminiai žodžiai: simbolis, religinė architektūra, šventykla, vertė, kaita.